A Content Analysis of Critical Reading Skills and Reading Passages in Critical Reading Textbook - Tri Angkarini; Susilowati Susilowati; Hermariyanti Kusumadewi (Scope : Journal of English Language Teaching, 2023)
The purpose of this research is to analyze the compatibility between the critical reading skills and the reading passages in the textbook with the syllabus and global Sustainable Development Goals (SDG) topics. The method used in this research was a qualitative descriptive method that utilized the critical reading textbook as a sample. The sample of the research was taken by using a checklist and the result of the research will be shown by percentages. The results find that the textbook has 100% compatibility with all of the criteria in the syllabus and has only 47.05% compatibility with the SDGs topics. It means that this textbook is recommended to be used as one of the teaching references in critical reading courses but the authors are suggested to construct some adjustments so that students will get the latest reading material as the times change which is related to SDGs in order to foster the students’ awareness, empathy, and compassion in facing global issues.